Archaeomineralogy - Rapp, George. (Natural Science in Archaeology, 2009)
Archaeomineralogy provides a wealth of information for mineralogists, geologists and archaeologists involved in archaeometric stuides of our past. The first edition was very well recieved and praised for its systematic description of the rocks and minerals used througout the world by our ancestors and for its excellent list of over 500 references, providing easy access to the fields of archaeomineralogy and geoacrchaeology. This second edition of Archaeomineralogy takes an updated and expanded look at the human use of rocks and minerals from the Paleolithic through to the 18th century ACE. It retains the structure and main themes of the original edition but has been revised and expanded with more than 200 new references in the text, a bibliography of useful references not included in the text, a dozen new figures (drawings and photos), coverage of many additional important mineral, rock, and gem materials, increased geographic scope, particularly but not limited to Eastern Europe, and a more thorough review of early contributions to archaeomineralogy especially those of Agricola.